(untitled) (Islamic Sciences Journal, 2025)
The research demonstrates the role of the Prophetic Sunnah in promoting personal development and sustainable learning, and how the teachings of the Prophet Muhammad (peace and blessings be upon him) can contribute to building a sustainable scientific community through an individual’s commitment to ethical and practical values. The research presents how to understand the Prophetic Sunnah from an educational and developmental perspective, highlighting how to apply the teachings of the Prophetic Sunnah in the fields of education and teaching. It also highlights the Prophetic hadiths that motivate the constant pursuit of knowledge and self-development, as well as encouraging society to adopt the values ​​of knowledge and continuous work. The research also seeks to provide a vision on how contemporary society can benefit from these Prophetic teachings for the sake of scientific advancement and innovation in various fields, achieving the construction of a scientific community capable of innovation and sustainable development. The research is divided as follows: Section One: Introduction to the Prophetic Sunnah and its importance in personal life. Section Two: The role of the Prophetic Sunnah in promoting personal development and sustainable learning. Section Three: Applications of the Prophetic Sunnah in building a scientific community: The Prophetic Sunnah and building a scientific community.